BIOELECTRICAL PRODUCTION BY MICROBIAL NANOWIRES - Omar Adel Badawi Omar; Faysal Raed Abd Al Rahim; Salam Adil Abduljabar Saed; Yousif Zeyad Yassen Daoud; Abd Alrahman Mohammed Jasim Mohammed (Journal of Medical Genetics and Clinical Biology, 2024)
Bacterial nanowires, which are electrically conductive appendages or threads that facilitate the transfer of electrons outside the bacterial cell, produced by a number of bacteria, have shown the potential to be useful in many fields, especially bioenergy and bioremediation. Bacteria have developed a group of nanowires in different forms, including Pilli, which are fine structures protruding from the surface of bacteria and used for adhesion, movement, and the formation of biofilms in some species that participate in extracellular respiration and use their filaments to transfer electrons. The world is currently witnessing an energy crisis due to the continuous increase in energy requirements around the world, so the trend today is to use microbial fuel cell (MFC) technology, which is an encouraging technology for generating electricity and a source of clean and environmentally friendly energy that uses microorganisms to convert the chemical energy of organic compounds into electricity using bacterial nanowires. Most MFC studies are being done for electricity generation, which is the primary application of the technology at the moment, and it is a fascinating technology that can use a variety of substrates, MFC cell with bacteria to achieve bioenergy production despite the fact that the energy levels in all these systems were relatively low